The Handheld Library: Developments at the Rector Gabriel Ferraté Library, UPC - Juan, Beatriz Benítez; Campos, Javier Clavero; Vila, Miquel Codina; Gálvez, Andrés Pérez (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
The purpose of this paper is to highlight the mobile services developed by the Rector Gabriel Ferraté Library (BRGF) of the Universitat Politècnica de Catalunya (UPC-Barcelona Tech) in Barcelona, Spain. We hope this paper will be of use to other libraries exploring new technologies for communicating and delivering their services to users at a time when mobile services are an emerging topic in librarianship and information science literature. By setting out the successive steps involved in the as yet unfinished process of building our mobile services portfolio, we aim to offer a detailed picture of the mobile services and features offered by a university library from a case study perspective. The main topics to be discussed include: The BRGF’s mobile website, including the information available, its interactive capabilities and the services it provides to its users. The mobile-friendly version of UP Commons(the UPC Library Service’s institutional repositories). The UPC Library Service’s mobile OPAC. The mobile version of u-win(BRGF’s videogame service). The use of QR codes to deliver information to mobile devices. Text message notifications. Additional topics for discussion include: The library’s organisation and the organisational concepts that underpin and make possible its technological developments (including mobile). BRGF’s concern regarding the reduction of investment in the development of mobile services. The criteria and tools used to guide the library’s decisions regarding the design and orientation of current and future mobile services. How mobile services can help to improve the image of the library as a leading technology site. Selected mobile features that BRGF plans to offer in the near future. Ultimately, this paper aims to delineate the effectiveness and potential of delivering library services by the preferred means of communication of a new generation of students and teachers.